Degradation of SAMHD1 Restriction Factor Through Cullin-Ring E3 Ligase Complexes During Human Cytomegalovirus Infection - Hyeon, Seokhwan; Lee, Myoung Kyu; Kim, Young-Eui; Lee, Gwang Myeong; Ahn, Jin-Hyun (Frontiers in Cellular and Infection Microbiology, 2020)
Sterile alpha motif (SAM) and histidine-aspartate (HD) domain-containing protein 1 (SAMHD1) acts as a restriction factor for several RNA and DNA viruses by limiting the intracellular pool of deoxynucleoside triphosphates and/or functioning as a nuclease. Here, we show that SAMHD1 suppresses the growth of human cytomegalovirus (HCMV), but its expression is downregulated partly at the protein level during viral infection. SAMHD1 knockdown using shRNA increased HCMV growth in human fibroblasts by 7- to 9-fold, confirming its anti-HCMV activity. We also found that the level of SAMHD1 was initially increased by HCMV infection but decreased partly at the protein level at late stages of infection. SAMHD1 loss was not observed with UV-inactivated virus and required viral DNA replication, indicating a role of viral late gene expression. This reduction of SAMHD1 was effectively blocked by MLN4924, an inhibitor of the Cullin-RING-E3 ligase (CRL) complexes. Further analysis with inhibitors demonstrated that SAMHD1 loss during HCMV infection was partly inhibited by MG132 but not bafilomycin A1 at all, suggesting the involvement of non-lysosomal degradation in this process. The CRL-mediated SAMHD1 loss at late times of virus infection was also observed by cell staining. Knockdown of CUL2 and to a lesser extent CUL1 using siRNA stabilized SAMHD1 and inhibited SAMHD1 loss during virus infection. Altogether, our results demonstrate that SAMHD1 inhibits the growth of HCMV, but HCMV induces degradation of SAMHD1 at late stages of viral infection through the CRL complexes.